(3GdfXGe GdbGfhfj ddeMce aj GdJMcje GdJLGQj GdOhdj (B/ s - (3fGUQ eMeO YHOGdYRjR GdTQeGf s; (3SGei YHOGdHGbi eMeO (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B-(3LGeYI GdbGgQI,s, 2012)
(3JJfGhd GdQSGdI ehVhY GdfXGe GdbGfhfj ddeMce aj GdJMcje GdJLGQj GdOhdj; MjK JHOC HaUd JegjOj jTQM eGgjI GdJMcje hCfhGYg hOhdjJg, Ke GdHGH GdChd GdPj jHjf VhGHW GNJjGQ GdeMce, hCNjQG GdHGH GdKGfj GdPj jTQM SdWGJ GdeMce hUdGMjJg(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2012.s
(3HHdjhLQGajG(B: (3UaMGJ(B368-391.s
Keywords: (3eGgjI GdJMcje s; (3GdJYQja HGdJMcje heHQQGJg s; (3CfhGY GdJMcjes; (3OhdjI GdJMcje GdJLGQjs; (3eYGjjQ JMOjO GdUaI GdOhdjI ddJMcje GdJLGQjs; (3SdWI GdeMce aj EUOGQ Mce GdJMcjes; (3GdTQhW GdhGLH JhGaQgG HGdeMce hWQb GNJjGQgs; (3eGgjI GdJMcje s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2012